Motif Pendiri Public Speaking “Sing Your Mind” Terhadap Public Speaking Anggotanya - Moch Wildan Hendra Kusuma; Ratna Puspita Sari (DIGICOM : Jurnal Komunikasi dan Media, 2022)
This research is entitled "Motives of Public Speaking Training Against Members of the SING YOUR MIND Community". This public speaking phenomenon still seems to be a scourge for some people. Especially the members of SING YOUR MIND, who before they joined the community, did not have public speaking skills and lacked confidence. So, in the “SING YOUR MIND” community, they learn and hone their public speaking skills. The purpose of this research is to find out the motives for implementing the training that is applied by this community, so that community members can be more confident in their public speaking skills. The research method used in this research is qualitative research with a phenomenology study approach. Data collection techniques by observation, interviews, and documentation of community activities SING YOUR MIND. The results of the study used purposive sampling. In this study, the researcher concluded that the training motive provided by the “SING YOUR MIND” community made members more confident with their public speaking skills.